THE APPLICATION OF DISCUSSION METHOD TYPES THINK PAIR SHARE (TPS) TO ENHANCE CRITICAL THINKING SKILLS OF STUDENTS IN SOCIAL STUDIES LEARNING - Putra, Rizki Septiyadi (2016)
The research was distributed by the researchers found upon observation in class VIII-B Junior High School Atikan Sunda Foundation, Bandung. The researchers found some weak indication of critical thinking skills of students in Social Studies learning. This is apparent from a study focused on the teacher, there are fewer students activity in the classroom, yet as students answer questions posed by teachers using their own analysis, students were glued to the textbook and the questions asked by students only as in their memory. An alternative problem solving become the choice of researchers that is by applying the method of discussion type think pair and share, where the teacher gives a series of questions to generate critical thinking ability of the students whether oral or written. Reviewing the problems that will be examined is related to the learning process, so the researcher chooses Classroom Action Research by Kemmis and Mc. Taggart model in four cycles. Increase critical thinking skills of students in class VIII-B Junior High School Atikan Sunda Foundation through discussion method types think pair share can be said to be successful. The Successful in this research are seen from an increase in the quantity and quality of critical thinking skills of students who demonstrated through the development of the aspects or several indicators of critical thinking skills. Based on the data in field research results can be drawn the conclusions of this study; first, condition classes into fun and students actively learning. Second, research planning is well designed. Third, the application of critical thinking skills through improved methods of discussion type think pair share held and the more directional on any cycle. Fourth, after implementing the methods of discussion type think pair share can grow and interest of students in learning Social Studies.;Penelitian ini dilatarbelakangi oleh permasalahan yang ditemukan peneliti pada saat observasi awal di kelas VIII B SMP Yayasan Atikan Sunda kota Bandung. Berdasarkan hasil observasi, peneliti menemukan beberapa indikasi lemahnya keterampilan berpikir kritis siswa dalam pembelajaran IPS. Hal ini terlihat dari pembelajaran yang terfokus pada guru atau teacher center, kurang aktifnya siswa di dalam kelas, belum mampunya siswa menjawab pertanyaan yang diajukan oleh guru dengan menggunakan analisisnya sendiri, siswa terpaku kepada buku teks dan pertanyaan yang diajukan siswa hanya sebatas pada tataran ingatan. Alternatif pemecahan masalah yang menjadi pilihan peneliti yaitu dengan menerapkan metode diskusi tipe think pair and share, dimana guru memberikan serangkaian pertanyaan untuk membangkitkan kemampuan berpikir kritis siswa baik secara lisan maupun tertulis. Meninjau permasalahan yang akan diteliti berkaitan dengan proses pembelajaran, maka peneliti memilih Penelitian Tindakan Kelas (PTK) dengan model Kemmis Mc. Taggart yang dilakukan dalam 4 siklus. Peningkatan keterampilan berpikir kritis siswa di kelas VIII B SMP Yayasan Atikan Sunda Kota Bandung melalui metode diskusi tipe think pair and share dapat dikatakan berhasil. Berhasilnya penelitian ini dilihat dari adanya peningkatan kuantitas dan kualitas keterampilan berpikir kritis siswa yang ditunjukkan melalui perkembangan aspek-aspek atau beberapa indikator keterampilan berpikir kritis. Berdasarkan data hasil penelitian dilapangan dapat ditarik kesimpulan dari penelitian ini, antara lain pertama, kondisi kelas menjadi menyenangkan dan siswa ikut aktif saat pembelajaran berlangsung. Kedua, perencanaan penelitian dirancang dengan baik. Ketiga, penerapan peningkatan keterampilan berpikir kritis melalui metode diskusi tipe think pair and share dilaksanakan semakin terarah pada setiap siklusnya. Keempat, setelah diterapkannya metode diskusi tipe think pair and share dapat menumbuhkan minat siswa dalam pembelajaran IPS sehingga penelitian untuk meningkatkan keterampilan berpikir kritis siswa berjalan dengan baik.